School dropout: characterization of the conditions of students at a Portuguese higher education institution - Lopes, Marina (2022)
Entry into higher education is the beginning of major changes and adaptations in which issues such as a new life context, the demands of autonomy and independence, the motivations and personal interests of the new student emerge. Consequently, not only academic, but also social and psychological difficulties may also appear. This study aimed to analyse the perception of students enrolled in a Portuguese higher education institution about their condition regarding the difficulties in the areas related to the adversities of entering higher education, as well as their personal difficulties and resources, and their availability to collaborate in a volunteer project for dropout prevention. This study was designed based on the perspective that all individuals have relevant resources for the community, it is understood that each student, regardless of the needs or vulnerabilities that he/she may present at a given moment, has resources whose sharing is an added value for the good of the academic community (mainly for reducing school dropout). Therefore, a quantitative study was carried out using a questionnaire developed for this purpose, which allows the identification of the needs and resources of the students, as well as their availability to participate in volunteer programs with a view to suppressing the needs or necessities of their colleagues. A total of 825 students participated, being 58,91% (n=486) were females and 41,09% (n=339) were males, of 26 nationalities, being the majority (87,64%) Portuguese. The majority (59,52%) live in a place different from the usual one, therefore being students from other Portuguese locations or from abroad, and study in graduation courses (68,24%). After the analysis of the results it was possible to conclude that: a) 47,40% of the students are aware of among one and four situations of dropping out of the higher education institution; b) Adversities in entering higher education are felt by more than half of the students respondents, with 63,05% of students reporting feeling difficulties in accessing information inherent to enrolment, registration and social action services, 50,19% difficulties in spatial orientation within the campus when entering the institution and 55,08% difficulties in recognizing the city when entering the institution; c) More than half of the student respondents report having difficulties at academic level (73,49%), at personal and/or interpersonal level (64,18%) and in securing material goods (55,48%); d) 41% of the student respondents showed interest in participating in a volunteering project at the higher education institution in question; e) Most of the students who indicate having difficulties at different levels (72,91%) are available to collaborate in exchange for the support they would like to receive. A volunteer project will certainly be an added value in the scope of the different difficulties expressed by the students in this research, both at the level of the most mentioned by the students, and at the level of those that, being more residual, are still important. A project of this kind should encompass those who have shown willingness to participate voluntarily without needing anything in return and those who, being potential beneficiaries, also have available resources to meet the needs of others.